Avaliação da relação GGT: creatinina urinária em cães com Ehrlichia spp. - Barbosa, Giovanna Valverde Magalhães [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Ehrlichia spp. is a genus of bacteria that can be transmitted to dogs through the bite of the Rhipicephalus sanguineus tick, causing clinical symptoms such as anorexia, lethargy, and splenomegaly; laboratory alterations like thrombocytopenia and anemia; and complications secondary to the infection, one of which is acute renal injury (AKI). AKI in infectious diseases may be related to glomerulonephritis caused by the deposition of immune complexes, but there are reports of tubular renal injury also affecting these patients, as seen in dogs with visceral leishmaniasis. The urinary GGT:creatinine ratio is an early and persistent marker of tubular renal injury, detecting this alteration even in patients with serum creatinine within reference values. Urinalysis and urinary GGT:creatinine ratio tests were performed on 10 healthy dogs and 10 dogs positive for Ehrlichia spp., which revealed statistically significant differences (p < 0.001) in the urinary GGT:creatinine ratio values between the two groups, confirming tubular injury in these patients. Urinary clusterin and cystatin B are also markers of tubular renal injury and have been measured in patients with Ehrlichia spp.; however, their high cost compared to the urinary GGT:creatinine ratio makes their use in clinical practice unfeasible. Therefore, the urinary GGT:creatinine ratio emerges as a tool that can be used as a marker of tubular injury in dogs with Ehrlichia spp., as it requires equipment and reagents already used in laboratory routines, is low-cost compared to other biomarkers, and allows early diagnosis of renal injury.

A Ehrlichia spp. é um gênero de bactérias que podem ser transmitidas aos cães pela picada do carrapato da espécie Rhipicephalus sanguineus e causar sintomatologia clínica como anorexia, letargia e esplenomegalia; alterações laboratoriais como a trombocitopenia e a anemia; e complicações secundárias à infecção, sendo uma delas a injúria renal aguda (IRA). A IRA, em doenças infecciosas, pode estar relacionada à glomerulonefrite gerada a partir da deposição de imunocomplexos, mas há relatos de lesão tubular renal também acometer esses pacientes, como em cães com leishmaniose visceral. A relação GGT:creatinina urinária é um marcador precoce e persistente de lesão tubular renal, detectando esta alteração mesmo em pacientes com creatinina sérica dentro dos valores de referência. Foram realizados exames de urinálise e relação GGT:creatinina urinária em 10 cães saudáveis e 10 cães positivos para Ehrlichia spp., que constataram diferenças estatísticas (p < 0,001) dos valores da relação GGT:creatinina urinária entre os dois grupos, que permitiu atestar a lesão tubular nestes pacientes. Clusterina e cistatina B urinária também são marcadores de lesão tubular renal e já foram dosados em pacientes com Ehrlichia spp., no entanto, seu alto custo, quando comparado à relação GGT:creatinina urinária, torna seu uso na rotina clínica inviável. A relação GGT:creatinina urinária, portanto, vem como uma ferramenta passível de ser utilizada como marcador da lesão tubular em cães com Ehrlichia spp., uma vez que requer equipamentos e reagentes já utilizados nas rotinas laboratoriais, possui baixo custo quando comparada a outros biomarcadores, além de permitir o diagnóstico precoce da injúria renal.
Evaluation of the urinary ggt: creatinine ratio in dogs with Ehrlichia spp.
Keywords: cães; rins; bioquímico